Artificial Orthogonalization in Regression Analysis - McCallum, B. T. (The Review of Economics and Statistics, 1970)
posed to the balanced growth advance along all fronts. Both of these arguments would involve an association between G in the current period and V's in previous periods. Even if Swamy's results falsify the balanced growth theory (which is very much in doubt), they do nothing to support its alternative, the unbalanced growth strategy. A more meaningful approach would be the estimation of Gt = f (Vt-mn .-... Vt-n) where t m and t n bound the time period considered relevant to Gt.